Analysis in ESG Rating Agencies Motivation in the Process of Formulating the ESG Index: Institutional Logics - Indahna Sulfa; Elvia R. Shauki (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study aims to evaluate the applications of institutional logic on the motivation of the Kehati Foundation in formulating a different ESG (Environment, Social, Governance) Index compared to other ESG rating agencies. The research methodology used a case study as a research strategy and a qualitative research approach with a single unit of analysis design namely Kehati Foundation. The result explains that the Kehati Foundation, in formulating the different ESG indexes compared to other rating agencies was motivated by the domination of externality (symbolic carriers) towards internality (material carriers), multiple logics that came from professional, market, self-regulatory, and sustainability logics, subsequently the dominant logics contributed by professional logics, and then competing logics between actor, routines and OPM ESG Index Scoring. The implication of the study is to demonstrate a significant positive impact in promoting sustainable investment and gaining the trust of investors (both potential and existing investors) which are expected to obtain adequate confidence in making investment decisions and to develop business practices for rating agencies. This study contributes an extensive ongoing development for future research which is currently still very limited.